2022
DOI: 10.1063/5.0096784
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of generating quasi-static magnetic fields using laser-driven “capacitor” coils

Abstract: Over the previous decade, numerous experiments have been performed using a laser to drive a strong, quasi-static magnetic field. Field strength and energy density measurements of these experiments have varied by many orders of magnitude, painting a confusing picture of the effectiveness of these laser-driven coils (LDCs) as tools for generating consistent fields. At the higher end of the field energy spectrum, kilotesla field measurements have been used to justify future experimental platforms, theoretical wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…A different method for creating magnetic fields with laserplasma interactions is through laser-driven coils (Gao et al, 2016;Peebles et al, 2022). In this approach, a laser is used to heat and eject electrons from a plate so that a current is drawn through a loop connected to the plate.…”
Section: A Magnetic-field Generationmentioning
confidence: 99%
“…A different method for creating magnetic fields with laserplasma interactions is through laser-driven coils (Gao et al, 2016;Peebles et al, 2022). In this approach, a laser is used to heat and eject electrons from a plate so that a current is drawn through a loop connected to the plate.…”
Section: A Magnetic-field Generationmentioning
confidence: 99%
“…An external magnetic field was applied to the plasma in several shots of the heating experiment. A laser-driven coil [32][33][34] was used to converge the REB and increase heating efficiency [27]. The laser-driven coil consisted of two plates and an attached coil.…”
Section: Experimental Configurationsmentioning
confidence: 99%
“…Recently, Peebles et al [37] conducted comprehensive experiments to evaluate the capability of laserdriven coils in generating magnetic field by using various diagnostic methods mentioned above. As a conclusion, it has been found that the laser driven coils do not perform as claimed, failed to produce quasi-static kilotesla-level magnetic fields and are not applicable for the majority of current experiments where it is beneficial to have a field.…”
Section: Introductionmentioning
confidence: 99%